Physical and spiritual cleanliness in islamic perspective: relationship and effectiveness to the health in preventing covid-19 plague / Zanirah Mustafa@Busu ...[et al.]. - Mustafa@Busu, Zanirah; Nik Din, Nik Muniyati; Junoh, Noraini; Hisham, Zainab; Muhammad Hashim, Nurhidayah; Nik Wan, Nik Zam; Yusoff, Zulkarnain (2022)
The emphasis on cleanliness is an important foundation of faith because faith and cleanliness are intertwined. Every Muslim is obliged to maintain cleanliness as it is an obligation as a Muslim. A good Muslim and believer will maintain the cleanliness of the physical and spiritual nature of the physical and spiritual to form a true believer. At the same time, it can be a bulwark in preventing COVID-19 outbreak infection. Since this pandemic leads to uncertainties that can affect the health and needs of living as a Muslim, this study will debate physical and spiritual hygiene to know the concept of hygiene about the physical and spiritual aspects from the perspective of Fiqh Islam. In addition, this article also aims to examine the relationship between physical and spiritual hygiene as well as its effectiveness on the health of Muslims to protect themselves from COVID-19 infection. The data was obtained from library studies through journal articles, reference books, thurath books, reports, and documentation from the Ministry of Health Malaysia and Kelantan State Health Department. Personal hygiene and healthy living will help in carrying out the duties of a Muslim in the daily routine especially in the new era of norms. The findings show that a) there is a significant demand for physical and spiritual personal hygiene practices according to Islamic Fiqh as well as complete Islamic guidance on health in terms of care, preservation, and control to protect against COVID-19 infection and b) there are positive influences and consistent effective practices of physical and spiritual hygiene. We can take control measures to develop mandatory activities under the new norm, especially to prevent all infectious diseases including the COVID-19 pandemic. Therefore, every Muslim should be maintained and consistent in maintaining the cleanliness practices of both the physical and the inner, so that it will be a shield against all dangerous epidemics.